New method to interpret the 'canister test' data for determining kinetic parameters of coalbed gas: theory and experiment. Issue 13 (23rd December 2021) - Karchevsky, A. L.; Nazarov, L. A.; Nazarova, L. A.
Abstract : The nonlinear model has been developed and implemented to describe gas emission from coal slack placed in a sealed container ('canister test'). The model accounts for initial gas content S, coefficients of diffusion D, mass transfer β and desorption kinetics γ, as well as for fractional composition of the sample. Using the developed analytical method of the initial boundary value problem solution, it is found that the pressure P ( t ) of gas in the container tends to a constant value with time. The inverse problem of determining the kinetic parameters S, D, β and γ of gas by the pressure P ( t ) readouts in the experiments has been formulated and subjected to solvability tests. The introduced objective function (discrepancy between P ( t ) and the calculated pressure) is almost independent of β . Based on the modification of the conjugate gradient method, the inverse problem algorithm is proposed. Using the data of in situ measurements of pressure in three containers, the authors perform quantification of gas content, as well as diffusion and desorption kinetics coefficients in terms of a coal bed in Berezovskaya Mine (Kuznetsk Coal Basin). The range of the mass transfer coefficient is estimated by the results of the grain-size analysis of the test samples.